Aloysius learnt Irish language and botany by himself, reported by The Atlantic Advocate - Mannion,Maura (1983)
Joan Weeks, the author of this article, "a walking Encyclopedia of Botany, Language" introduced the history of O'Brien family and farm generally at the start. Then he introduced how and why Aloysius learnt Irish Gaelic and botany by himself. Dr. John Mannion, who studied Irish culture on eastern Canada, gathered much information from Aloysius for his PhD dissertation.